Pentingnya Kesejahteraan Emosional di Dunia Pendidikan - Fadhlan Mubarak; Yullys Helsa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Emotional well-being is a fundamental aspect in the field of education that plays a crucial role in supporting academic achievement, learning motivation, and students' social development. This article discusses the definition and concept of emotional well-being, its influence on academic success, and the role of Social Emotional Learning (SEL) and teachers as key facilitators in enhancing students' emotional well-being. Furthermore, the article examines the challenges faced in implementing emotional well-being in schools, as well as educational strategies and policies that support it. Using a literature review methodology, this article collects and analyzes recent sources from journals and official reports. The findings indicate that integrating emotional well-being into education not only improves learning outcomes but also provides long-term benefits for mental health and students' preparedness for the future. Therefore, it is crucial for educational institutions to prioritize emotional well-being as an integral part of the learning process.